Learning Innovation Training (PAIKEM) Physical Education based on the 2013 Curriculum for PJOK Teachers - Muhammad Sukron Fauzi; Didik Cahyono; Jance J Sapulete; Naheria (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of the training is (a) it is hoped that PJOK teachers will understand the latest physical education paradigm and the learning process. (b) After actively participating in training activities, it is hoped that elementary school PJOK teachers will gain theoretical and practical experience regarding PIKEM learning in physical education through play models and modification of learning facilities so that they can be applied and developed in their respective schools. This community service method is carried out by providing training to teachers regarding active, innovative, and fun PJOK learning and making PJOK learning media by modifying fun learning infrastructure tools and game models so that children don't get bored and bored quickly. The results of this service, the free test ability level was found that 50% of PJOK teachers' knowledge related to theory and practice of Physical Education learning was classified as low category, while after being given training, 83% post test results were classified as high category. Effective and Fun (PAIKEM) Physical Education Based on the 2013 Curriculum and teachers can innovate in physical education learning. And they promised to start carrying out motivation and fun learning after receiving this counseling.